(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The article examines the impact of artificial intelligence (AI) on the teaching of Russian as a Foreign Language (RFL). It analyzes the possibilities of applying AI technologies in the educational process, including automated assessment, personalized learning, and the development of interactive educational materials. The study discusses potential risks related to ethical concerns, information reliability, and the possible reduction of the teacher’s role. It also identifies prospects for integrating AI into the RFL teaching system, including the development of adaptive platforms and hybrid learning models.